Three Dimensional Global Counter-Terror Policy Response: Assessing the Efficacy of Pakistan’s National Action Plan - Muhammad Idrees; Manzoor Ahmad Naazer, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
From 2001 to 2014, Pakistan initiated different short term counter terrorism strategies e.g. military operations and negotiations but most of the time these efforts proved to be short lived and militancy spoke at length with intervals. The establishment of NACTA in 2009 was supposed to work as a bridge between state security enforcement and intelligence agencies and government policy wings for curbing the menace of terrorism and extremism. In 2013, the authority was made the major state agency to combine state and security agencies response to counter terrorism and extremism. But still there was lack of a broader and all out CT-Policy. It took almost thirteen years’ time span to come up with a national policy on homeland security, namely the National Internal Security Policy-14 (NISP-2014). The late enactment and lack of coordination in the implementation did not stop the devastating Army Public School incident which regenerated the debate about CT-Policy, which ultimately resulted in devising a comprehensive and broader policy; the National Action Plan ‘NAP-2014’. The policy is a specimen of national consensus by all important sections of Pakistani state, government and politics. This paper assesses the efficacy of NAP. Qualitative method of research is applied, the research relies mainly on printed and electronic sources and both primary and secondary sources are consulted in the completion of the study.